Species composition and abundance of leafrollers in a Canterbury pine plantation - Brockerhoff, E.G.; Jactel, H.; Leckie, A.C.; Suckling, D.M. (New Zealand Plant Protection, 2002)
Several leafroller species (Tortricidae) are known to occasionally cause considerable defoliation in Pinus radiata plantation forests We conducted pheromone trapping for five indigenous species Ctenopseustis herana Ctenopseustis obliquana Planotortrix excessana Planotortrix notophaea and Planotortrix octo and the exotic Epiphyas postvittana to determine their abundance in 20 P radiata stands in Eyrewell Forest North Canterbury Trapping from December 2001 to February 2002 indicated that E postvittana and C obliquana were very abundant (with mean catches of 077 and 044 moths/trap/day respectively) while the other species were rarely caught Results for the native leafrollers differ considerably from those reported from other plantation forests and other habitats in Canterbury such as apple orchards where P octo and C herana are generally more common